Pengembangan E-LKPD Berbasis Deep Learning Berbantuan Wizer.Me Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP - Aknes Monika; Dwi Oktaviana; Rahman Haryadi (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
The development of E-LKPD is motivated by the limitations of mathematics learning in schools that still rely on textual textbooks without adequate media or worksheets, resulting in low motivation and critical thinking skills of students. This study aims to describe the process of developing Electronic Student Worksheets (E-LKPD) based on Deep Learning assisted by Wizer.me to improve critical thinking skills on Cartesian coordinates material for eighth-grade junior high school students. This type of research is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) with research subjects of 26 eighth-grade students of SMP Negeri 1 Sompak. Data analysis techniques used include validity analysis, practicality, effectiveness using the Paired Sample T-Test, and analysis of improving critical thinking skills using the N-Gain Score. The results of the study show that the developed E-LKPD obtained a validity level of 90,51% with a very valid category and a practicality level of 87,02% with a very practical category. The results of the Paired Sample T-Test showed a value of t(25) = -16.353 with Sig. (2-tailed) of 0.000 < 0.05, so ?0 was rejected and ?1 was accepted, indicating a statistically significant improvement in students' critical thinking skills after the implementation of the Deep Learning-based E-LKPD assisted by Wizer.me. In addition, an average N-Gain Score of 0.56 was obtained with a moderate category, indicating that students' critical thinking abilities increased in the moderate category after using Deep Learning-based E-LKPD assisted by Wizer.me. Thus, Deep Learning-based ELKPD assisted by Wizer.me was declared valid, practical, effective, and able to improve students' critical thinking abilities.